Relationship of HIV Status and Fatigue, Cardiorespiratory Fitness, Myokines, and Physical Activity. (July 2019) - Webel, Allison R.; Jenkins, Trevor; Longenecker, Christopher T.; Vest, Marianne; Davey, Christine Horvat; Currie, Jackson; Darrah, Rebecca; Litman, Paul; Fernando de Oliveira, Vitor Hugo; Josephson, Richard A.
Abstract : Abstract: People living with HIV (PLWH) experience high rates of fatigue, which can be improved with physical activity. We examined relationships between HIV infection, fatigue, cardiorespiratory fitness, physical activity, and myokines. Twenty PLWH and 20 HIV-uninfected adults completed a fatigue assessment, a maximal cardiometabolic exercise test, serum measures of myokines, and wore an accelerometer for 7 days. Measures were completed at baseline, 3 months, and 6 months. At baseline, PLWH had more fatigue (4.7 ± 2.6 vs. 2.8 ± 2.5, p = .01) and higher peak ventilatory efficiency (VE/VCO2 ; 33 ± 5.5 vs. 30.2 ± 2.5; p = .06). Half of PLWH engaged in at least one 10-minute bout of physical activity in the previous week, compared with control subjects (65%). Over time, HIV infection and fibroblast growth factor 21 were associated with fatigue ( p < .05). People living with HIV have more fatigue and a higher ventilatory efficiency; expression of fibroblast growth factor 21 may underpin this relationship.